Lies in the Qur'an: Analysis of the Words Kādzib, 'Ifk, Zūr, Bāṭil, in the Tafsir Al-Tahrir Wa Al-Tanwir by Ibn 'Asyur - Pratiwi, Azzahra Rania; Hakiki, Kiki Muhamad; Alghifari, Abuzar; Muttaqin, Ahmad (Mauriduna : Journal of Islamic Studies, 2026)
This research is predicated on the sociological necessity of understanding the various forms of lies that are still taken seriously by society. It seeks to critically examine the semantic interpretations of the terms Kādzib, 'Ifk, Zūr, Bāṭil as articulated in the Tafsir al-Tahrir wa al-Tanwir by Ibnu 'Asyur. The research formulationis structured around two primary objects: 1) how ibn Asyur interprets the terms Kādzib, 'Ifk, Zūr, Bāṭil, and 2) how the hadith concerning the permissibility of lying is relavant to these meanings. Adopting a qualitative, library-based methodology, this study employs a thematic analysis method (maudhu'i). The primary source materials is Tafsir al-Taḥrīr wa al-Tanwīr by Ibn ‘Āshūr, supplemented by  a secondary source of relevant scholarly journals, monographs and theological treatises. The findings indicate that while these terms are oftern categorized under the broad umbrella of falsehood, each term has a distinct meaning depending on its context. According to Ibn 'Asyur, 1) Kādzib refers to act of deception. 2) 'ifk denotes major accusations or slander. 3) zūr refers to the distortion of information or testimonies that deviate from empirical reality. 4) bāṭil refers to any form of falsehood or something that lacks a foundation of truth. The Hadith that permits lying in three situations warfare, conflict resolutions, and the preservation of marital harmony. The study concludes that such exceptions do not constitute condemned mendacity, rather they serve as instruments of  maqāṣid al-syarī'ah to maintain social equilibrium and communal benefit. The scholarly contribution of this study lies in its systematic analysis of the varying gradations of lying through the lens of Ibn 'Asyur perspective. It offers significant insights into the development of thematic exegesis and provides a framework for the construction of social ethics, asserting that the morality of an utterance is intrinsically linked to its contextual purpose and its alignment with the preservation of public interest.